Stability Analysis and Heterotic Studies in Maize (Zea mays L.) Inbreds to Develop Hybrids With Low Phytic Acid and High-Quality Protein - Lydia Pramitha, J.; Joel, John; Rajasekaran, Ravikesavan; Uma, D.; Vinothana, Kumari; Balakrishnan, Meenakumari; Sathyasheela, K. R. V.; Muthurajan, Raveendran; Hossain, Firoz (Frontiers in Plant Science, 2022)
Maize is a major staple crop with high value as food and feed in the poultry sector. Considering the overall nutritional value, maize-based diets comprise two major constraints i.e., higher phytic acid and lack of tryptophan. To overcome these issues, a set of identified stable donors for low phytic acid and higher tryptophan were crossed in a line × tester fashion and the hybrids obtained were evaluated at three locations with two replications. Among the inbreds for yield, UMI 1201 and UMI 1205 were stable good combiners and for phytic acid, UMI 447 and LPA-2-285 were identified as efficient combiners across locations. Subsequently, 72 hybrids developed from these inbreds had a reduced phytate and higher tryptophan compared with checks having alterations in their yield levels. From AMMI and GGE biplots, DMR-QPM-09-13-1 × UMI 1099 (PA:9.38 mg/g, trp:0.06% & yield: 184.35 g) and UMI 1205 x UMI 467 (PA:7.04 mg/g, trp:0.06% & yield:166.39 g) were stable for their high yield with medium phytic acid and tryptophan. Also, across environments, UMI 1200 × UMI 467 had a stable average yield of 129.91 g along with the lowest phytic acid of 4.50 mg/g and higher tryptophan of 0.07%. Thus, these hybrids could be selected and evaluated in upcoming bio-fortification trials to benefit the poultry sector. Further, the parental inbreds utilized were grouped into heterotic pools to serve as a source population for the development of lpa hybrids in the future programs.